Escritores Digitales: Fortalecimiento de las prácticas de escritura en estudiantes de grado octavo del Colegio Colombo Florida Bilingüe a partir de una estrategia didáctica mediada por la multimodalidad y la plataforma online Wattpad (2023)
The present research entitled "DIGITAL WRITERS: Strengthening writing practices in eighth-grade students at the Colombo Florida Bilingual School, from a didactic strategy mediated by multimodality and the online platform Wattpad" arises due to the low performance of students in their writing processes within the subject of Spanish as it was observed from the diagnosis test to define the research problem.